THE RELATIONSHIP BETWEEN PERFECTIONISM AND HIGH INTELLECTUAL ABILITIES - Jokste, Inese; Koļesņikova, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Since the beginning of 1990s, when the first multidimensional concepts of perfectionism were published (see, Frost et al., 1990; Hewitt, & Flett, 1990, 1991) there has been a stable increase in the research of perfectionism and its relationships to wide variety of variables, for example, stress (Smith, Saklofske, Yan, & Sherry, 2017), personality traits (Cruce, Pashak, Handal, Munz, & Gfeller, 2012) coping strategies (Gnilka, McLaulin, Ashby, & Alle, 2017). It has to be noted that perfectionism researchers have turned their attention to both general and clinical populations, as well as specific groups, for example, individuals with high intellectual abilities or gifted individuals (e.g., Kornblum, & Ainely, 2005; Margot, & Rinn, 2016). The paper aims to review the studies focused on relationship between perfectionism and high intellectual abilities, and to see what variables are involved in this relationship. In the first section of the paper concepts and definitions of high intellectual abilities are described. In the second section of the paper perfectionism concepts are described. An in the third section of the paper the relationship between high intellectual abilities and perfectionism is analysed. The results of literature review will serve as theoretical background for studying individuals with high intellectual ability and perfectionistic personality traits.